2017
DOI: 10.1089/ars.2016.6778
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Pure Ergothioneine to Healthy Human Subjects: Uptake, Metabolism, and Effects on Biomarkers of Oxidative Damage and Inflammation

Abstract: The uptake and retention of ET by the body suggests an important physiological function. The decreasing trend of oxidative damage biomarkers is consistent with animal studies suggesting that ET may function as a major antioxidant but perhaps only under conditions of oxidative stress. Antioxid. Redox Signal. 26, 193-206.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(157 citation statements)
references
References 65 publications
10
145
1
1
Order By: Relevance
“…This extension in mean and maximal lifespan with ET treatment would equate to years when translated to a human lifespan, but more importantly, the increased healthspan would lead to a significant reduction in morbidity and societal burden. It should also be noted that numerous animal and human studies have demonstrated that blood and tissue levels of ET are capable of reaching millimolar levels hence validating the feasibility of the doses tested in the nematodes .…”
Section: Discussionmentioning
confidence: 84%
“…This extension in mean and maximal lifespan with ET treatment would equate to years when translated to a human lifespan, but more importantly, the increased healthspan would lead to a significant reduction in morbidity and societal burden. It should also be noted that numerous animal and human studies have demonstrated that blood and tissue levels of ET are capable of reaching millimolar levels hence validating the feasibility of the doses tested in the nematodes .…”
Section: Discussionmentioning
confidence: 84%
“…Ergothioneine can accumulate to high levels in some human and animal tissues, including red blood cells (with basal levels of ~ 125 μ m and ~ 220 μ m in human and mouse whole blood, respectively, and millimolar levels reported in red blood cells ), liver and spleen (with basal levels of ~ 350 μmol·g −1 tissue and ~ 100 μmol·g −1 tissue in mouse liver and spleen, respectively) . Our recent study demonstrated that when ET is orally administered to mice, it accumulates rapidly in the liver and blood cells but also enters most (or perhaps all) other tissues, including brain, heart, lung, kidney, spleen and eye.…”
Section: Ergothioneine In Tissues Extracellular Fluids and Cell Culturementioning
confidence: 97%
“…Dietary ET in animals (including humans) is absorbed by means of an intestinal transporter, OCTN1, that has a high degree of specificity . The same transporter then distributes ET to most or all body tissues: excretion from the body is slow and administered ET is highly retained in human and other animal body tissues and red blood cells . This implies that ET has a useful function, otherwise why absorb and retain it?…”
Section: Ergothioneine a Natural “Antioxidant”?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although not our subject here, the biology of ergothioneine (an antioxidant) is very interesting (see e.g. [126,199,[210][211][212]), with SLC22A4 -/-cells being very sensitive to oxidative stress, but the key point is that this analysis shows the likelihood that many transporters were actually selected on the basis of their ability to take up dietary, bioactive compounds that are effectively xenobiotics [213]. Cloning large libraries of chromosome fragments [94,214], and seeing their effects on export or productivity, or assessing genes with increased transcription in response to increased external metabolite concentrations [108,215] provide for other methods (see e.g.…”
Section: Figure 3 An Untargeted Metabolomics Strategy For Determininmentioning
confidence: 99%